2017
DOI: 10.1111/1755-0998.12709
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of regression methods for model selection in individual‐based landscape genetic analysis

Abstract: Anthropogenic migration barriers fragment many populations and limit the ability of species to respond to climate-induced biome shifts. Conservation actions designed to conserve habitat connectivity and mitigate barriers are needed to unite fragmented populations into larger, more viable metapopulations, and to allow species to track their climate envelope over time. Landscape genetic analysis provides an empirical means to infer landscape factors influencing gene flow and thereby inform such conservation acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 60 publications
5
154
1
Order By: Relevance
“…Mixed models were fitted using the maximum likelihood population effects (MPLE) parameterization (Clarke, Rothery, & Raybould, ) implemented in the R package lme4 (Bates, Mächler, Bolker, & Walker, ). A simulation study by Shirk, Landguth, and Cushman, (2018) has shown that this linear‐mixed‐effects‐model‐based method had a high accuracy in model selection.…”
Section: Methodsmentioning
confidence: 99%
“…Mixed models were fitted using the maximum likelihood population effects (MPLE) parameterization (Clarke, Rothery, & Raybould, ) implemented in the R package lme4 (Bates, Mächler, Bolker, & Walker, ). A simulation study by Shirk, Landguth, and Cushman, (2018) has shown that this linear‐mixed‐effects‐model‐based method had a high accuracy in model selection.…”
Section: Methodsmentioning
confidence: 99%
“…Associations between landscape resistance matrices and pairwise genetic distances were tested using linear mixed effect models incorporating a maximum likelihood population effects (MLPE) approach (Clarke, Rothery, & Raybould, ; Van Strien, Keller, & Holderegger, ) using the lme4 package in R. This method incorporates a random effect structure that accounts for the nonindependence among pairwise data, and has been shown recently to outperform other model selection methods for landscape genetics (Shirk, Landguth, & Cushman, ). Prior to fitting models, matrices of D ps were log–transformed to satisfy normality assumptions and all dependent and independent variables were rescaled to units of standard deviation and a mean of zero.…”
Section: Methodsmentioning
confidence: 99%
“…Pairwise genetic distance is the response and the scaled and centred pairwise effective distance is the predictor. The MLPE mixed effects parameterization accounts for non‐independence among the pairwise data (Clarke, Rothery, & Raybould, ), and Shirk, Landguth, and Cushman () recently found that MLPE models performed best in landscape genetic model selection among the seven regression methods assessed. An objective function, specified by the user, is obtained from the fitted MLPE model: log‐likelihood, AIC, or marginal R 2 (Nakagawa & Schielzeth, ). Steps 2–5 are repeated until the specified number of n individuals have been created. The genetic algorithm then conducts selection on the population, and the individuals with the best objective function values are carried over to the next generation to form the reproducing population (default = top 5% retained each generation).…”
Section: Descriptionmentioning
confidence: 99%